On the question of the institutionalisation of investment law (general provisions) - Kunitskaya, Olga M. (Journal of the Belarusian State University. Law, 2022)
The article deals with the issues of the emergence of institutionalisation from the point of view of the universal structure of law. In order to present the theoretical foundations of institutionalisation from emergence of the consideration of its relationship with related legal categories that have been formed to date. An analysis of various points of view, formulations regarding the use of signs and the formation of an institution of rights that may reﬂect its essence is made. Positions on the issue of the essence of complex legal institutionalisation, the place of a complex institution in the law-forming process, and its formal consolidation are explored and generalised. On the one hand, there is a need to integrate a comprehensive institutional education into the system of law, into one or another branch of law. On the other hand, a problem arises related to the impossibility of a complex institution formed by the norms of several branches of law to enter one of the branches, since the scope of the regulatory action of the norms integrated into it, based on their objective properties, cannot be limited by the subject and method of a separate branch of law. This article identifes and systematises the existing scientifc achievements in the feld of legal institutionalisation, determines the directions of their interpretation in relation to investment law in terms of the legitimacy and validity of the institutionalisation of complex branches of law.